Exploring Impacts of Gojek Application as a Sharing Economy Tool on Indonesian Economics and Society: Systematic Literature Review Approach - Gunawan, Leonardo (Journal of Ecohumanism, 2024)
Digitisation has changed many industries, including the sharing economy. Indonesian multi-service platform Gojek has transformed logistics, finance, and transport. Job creation, economic growth, and social dynamics are examined in this study of Gojek's effects on Indonesia's economy and society. Society, business leaders, and policymakers must understand Gojek's influence. The positive and negative effects of Gojek's expansion on Indonesia's economy and society must be assessed. This study sheds light on digital platforms in developing economies and informs regulatory and development strategies. Gojek has boosted Indonesia's GDP and job creation, according to the study. The platform has helped drivers, micro-entrepreneurs, and small businesses earn flexible income. Gojek has changed consumer behaviour by making many services easier to use. Future viability, regulation compliance, and competition are gig economy concerns. Indonesia's digital economy relies on Gojek, which changed social norms. Theory enhances understanding of developing market digital platform economies and their socioeconomic effects. This study advises policymakers and businesses on promoting innovation with regulatory constraints and inclusive growth with digital platforms. This study emphasises the need to continuously evaluate digital platforms like Gojek to ensure their positive impact on economic growth and social welfare. Future research should examine long-term effects and compare digital platforms in similar economic contexts.